COMPARISON OF MAINTENANCE OF AUTOMATIC AND CONVENTIONAL DRIP IRRIGATION SYSTEMS ON HORENSO CROPS (Greenhouse Keboenumiku Cibodas-Lembang): Perbandingan Maintenance Metode Sistem Irigasi Tetes Otomatis Dan Metode Konvesional Pada Tanaman Bayam Jepang/Horenso - Ibnu Isa, Fatwa; Pratiwi, Vitta (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
Drip irrigation systems are installed in drylands that can provide stable water so that water delivery is better. With the development of technology drip irrigation systems can be controlled automatically which includes electronic devices to command the state of a system. This research uses 2 methods, namely the conventional method and the automatic drip irrigation method which aims to determine the need for water and fertilizer in Japanese spinach/horenso plants and compare maintenance from cost, time and human labor. The results of the study of water released using conventional methods amounted to 29,228 liters and automatic drip irrigation method amounted to 10,000 liters. The difference of 19,228 liters with a percentage of 66.78%, it can be interpreted that the automatic drip irrigation method is more efficient. The fertilizer spent using the conventional method was 20,120 liters and the automatic drip irrigation method was 9,000. The difference of 11,120 liters with a percentage of 55.26%, it can be interpreted that the automatic drip irrigation method is more efficient. The need for water and fertilizer using the automatic drip irrigation system method is more efficient and effective because in giving it not too much is wasted than using conventional methods.